Adjustable Width Linear Combinational Scan Vector Decompression - Krishna, C. V.; Touba, Nur A. (International Conference on Computer Aided Design: Proceedings of the 2003 IEEE/ACM international conference on Computer-aided design; 09-13 Nov. 2003, 2003)
A new scheme for combinational linear expansion isproposed for decompression of scan vectors. It has thecapability to adjust the width of the linear expansion each clockcycle. This eliminates the requirement that every scan bit-slicebe in the output space of the linear decompressor. Depending onhow specified the current bit-slice is, the decompressor may loadall scan chains or may load only a subset of the scan chains.This provides the nice feature that any scan vector can begenerated using the proposed scheme regardless of the numberor distribution of the specified bits. Thus, the proposed schemeallows the use of any ATPG procedure without any constraints.Moreover, it allows greater compression to be achieved thanfixed width expansion techniques since the ratio of the number ofscan chains to the number of tester channels can be scaled muchlarger. A procedure for designing and optimizing the adjustablewidth decompression hardware and obtaining the compresseddata is described. Experimental data indicates that the proposedscheme is simple yet very effective.